Epilogue (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Dear Robert [Campbell],Well, you've got me thinking. Your brilliant reading of LvH gives me a better understanding of what I have done and not done, but I think (for now), I like the book in its current state more than you do.Grant me the indulgence of being a little defensive.I don’t long as you do for the bald statement of “a coherent thesis”. Perhaps it is best for the coherent thesis to remain anchored where it is, just off-shore, partially shrouded in mist. Is that not the charm of it – a bit of elusiveness that makes one discover as one reads, maybe twice, that the pairings Love versus Hope, Perimeter Block versus Linear Block, Continuous versus Ruptured, Heideggerian versus Cartesian, Cultural and Mythological versus Abstract, Metis versus Epistime are each the same theme restated? Isn’t elusiveness the only option for a 150 pound running back?My heroes chose elusiveness, not because they couldn't think straight: Nabokov’s disdain for “idea mongers”; Balanchine’s “it's about twenty-eight minutes”; Fellini’s mocking of “stringent, unassailable logic”.My (and all my Berkeley colleagues) thinking of Chris Alexander as something of a nut-case was based on observing his fifty year struggle to escape from the brilliant insights and modest truth of A City is Not a Tree that he wrote at age twenty-six. He really thought of himself as capable of “a coherent thesis” that explained everything.From the arrogance that thinks it knows all truth, O God of truth deliver us.Fond regards,Dan